Peningkatan Literasi Digital melalui Pelatihan Pembuatan Konten Edukasi Berbasis Teknologi Informasi di SMAN 7 Bandar Lampung - Marlina, Iin; Hendro Pramono, Doni Eko (Institut Informatika dan Bisnis Darmajaya, 2024)
This study aims to enhance digital literacy among high school students by conducting a training program on educational content creation using information technology tools. The program focuses on providing hands-on experience in video editing software, digital education platforms, and social media optimization for disseminating educational information effectively. A practical methodology was employed, including interactive workshops and guided project sessions. The results indicate a significant improvement in students' technical and creative abilities, as well as their understanding of how to use digital tools responsibly and effectively. The findings underscore the importance of integrating digital literacy training into high school curriculums to prepare students for the demands of a technology-driven world. This initiative is expected to contribute to the students' overall skill development and readiness for the digital era..Penelitian ini bertujuan untuk meningkatkan literasi digital siswa SMA melalui program pelatihan pembuatan konten edukasi berbasis teknologi informasi. Program ini berfokus pada pemberian pengalaman langsung dalam penggunaan perangkat lunak video editing, platform edukasi digital, dan optimalisasi media sosial untuk menyebarkan informasi edukasi secara efektif. Metodologi yang digunakan meliputi lokakarya interaktif dan sesi proyek terarah. Hasil penelitian menunjukkan peningkatan signifikan pada kemampuan teknis dan kreativitas siswa, serta pemahaman mereka tentang penggunaan alat digital secara bertanggung jawab dan efektif. Temuan ini menegaskan pentingnya pelatihan literasi digital dalam kurikulum SMA untuk mempersiapkan siswa menghadapi tuntutan dunia berbasis teknologi. Inisiatif ini diharapkan dapat berkontribusi pada pengembangan keterampilan siswa secara keseluruhan dan kesiapan mereka di era digital..